Cutaneous metastases of lung cancer. Issue 842 (December 1995) - Kamble, R.; Kumar, L.; Kochupillai, V.; Sharma, A.; Sandhoo, M. S.; Mohanti, B. K.
Abstract : The reported incidence of skin metastases from lung cancer varies from 2.8-7.5%. In the present study 8.7% of patients had skin metastases, with head and neck being the most common sites, nodular lesions the most common, and adenocarcinoma the most frequent histology. Although most patients develop these lesions during the course of a known progressive disease, they may be the presenting manifestation of a primary tumour in the lung. The occurrence of skin lesions in lung cancer announces an ominous prognosis. The response to chemotherapy is poor, possibly due to poor blood supply to the skin; monitoring response to chemotherapy, however, is easier when such lesions are present.